Pediatric Head and Neck Tumors Associated with Li-Fraumeni Syndrome. (February 2022) - Rodriguez, Kenny D.; Schneider, Kami Wolfe; Suttman, Alexandra; Garrington, Timothy; Jellins, Tennyson; Tholen, Kaitlyn; Francom, Christian R.; Herrmann, Brian W.
Introduction: Cancer predisposition syndromes are germline pathogenic variants in genes that greatly raise the risk of developing neoplastic diseases. One of the most well-known is Li-Fraumeni syndrome (LFS), which is due to pathogenic variants in the TP53 gene. Children with LFS have higher risks for multiple malignancies before adulthood, often with rare and aggressive subtypes. Objective: To examine head and neck manifestations of LFS in children treated at a tertiary children's hospital over a 20-year period. Methods: A retrospective review of LFS children with neoplastic disease presenting in traditional Otolaryngologic head and neck subsites from 2000 to 2019, with patient charts reviewed for relevant clinical, imaging, and operative data. Results: Of the 40 LFS patients initially identified, 27 neoplastic tumors were identified in 20 children within this cohort (20 primary, 7 second primary). Head and neck subsites aside from the brain or orbit were involved in 22% (6/27) of these tumors, representing 20% (4/20) of primary tumors and 29% (2/7) of second primary tumors. Both second primaries within the head and neck were within the radiation fields of the first primary tumor. The mean ages at primary and second primary diagnosis were 4.6 years (SD 3.5) and 12 years (SD 1.4), respectively. The male/female ratio was 1:6 among all patients with head and neck tumors. All 6 head and neck tumors were sarcomas. Rhabdomyosarcoma ( N  = 3, 50%) was the most common pathology, and the other 3 demonstrated rare tumor pathological subtypes (synovial cell sarcoma, pleomorphic myxoid liposarcoma, mandibular osteosarcoma). The neck was the most common subsite (75%) within this group for primary tumor presentation. Conclusion: This study identifies a high potential for head and neck involvement in children with LFS, which has not been previously described in the literature. Otolaryngological care should be included in a multidisciplinary care team surveilling these patients.